2010
DOI: 10.1111/j.1540-8167.2009.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Multicenter Comparison on Health‐Related Quality of Life: The Value of Add‐On Arrhythmia Surgery in Patients with Paroxysmal, Permanent or Persistent Atrial Fibrillation Undergoing Valvular and/or Coronary Bypass Surgery

Abstract: Health-related quality of life in patients with paroxysmal, permanent and persistent atrial fibrillation improves after cardiac surgery regardless of giving add-on surgery or not, but this improvement is presumably more affected by treating the underlying heart disease than by restoring sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In this latter study, only 2 questionnaires were used and there was no comparison between patients with paroxysmal and persistent AF. In an additional study by Van Breugel et al , 32 patients who underwent cardiac surgery were randomly assigned to additional arrhythmia surgery. Both groups showed stable sinus rhythm in 62% regardless of arrhythmia surgery after 12 months and both groups showed a significant improvement in the SF 36, the multidimensional Fatigue Inventory 20 and the Euro QoL (EQ‐5D + VAS) regardless of the arrhythmia surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this latter study, only 2 questionnaires were used and there was no comparison between patients with paroxysmal and persistent AF. In an additional study by Van Breugel et al , 32 patients who underwent cardiac surgery were randomly assigned to additional arrhythmia surgery. Both groups showed stable sinus rhythm in 62% regardless of arrhythmia surgery after 12 months and both groups showed a significant improvement in the SF 36, the multidimensional Fatigue Inventory 20 and the Euro QoL (EQ‐5D + VAS) regardless of the arrhythmia surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 905 studies were identified from the original PubMed search, of which 300 were reviewed in depth for inclusion, and 38 studies ultimately met all inclusion criteria. [10][11][12][13][14][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]40,42,[48][49][50][51][52][53][54][55][56][57] The remaining 262 studies were excluded because of no comparison group (n ¼ 245), case report (n ¼ 7), no outcome (n ¼ 6), or duplicate data from the same investigators (n ¼ 4).…”
Section: Methods Of Reviewmentioning
confidence: 99%
“…Pre- and postoperative clinical data were used from the patients enrolled in the ASAF trial [7]. Based on their rhythm outcome patients were divided in two groups: SR at 12 months follow up (SR 12 ) or AF at 12 months follow up (non-SR 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on their rhythm outcome patients were divided in two groups: SR at 12 months follow up (SR 12 ) or AF at 12 months follow up (non-SR 12 ). Antiarrhythmic and anticoagulant protocols were as previously reported [7]. Patients were seen at the outpatient clinic 3 months, 6 months, and 12 months after the surgical procedure, and annually thereafter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation